Polyherbal Anti-dandruff Shampoo: Basic Concept, Benefits, and Challenges - Patidar, Dr. Kalpana (Asian Journal of Pharmaceutics (AJP), 2018)
The objective of this review article is to provide information about various herbs used in dandruff treatment along with causes and remedies of dandruff formation. This article also highlights the benefits of herbal shampoo over synthetic shampoos. The hair is an integral part of the way to feel about the self-appearance, and when the hairs are lost, it can be damaging to self-esteem and self-confidence. One common reason is dandruff; a very common scalp disorder with high prevalence in population is caused by numerous host factors in conjunction with Malassezia furfur. Most of the commercially available anti-dandruff hair shampoos contain some form of antifungal agents that appear to reduce the incidence of the disease. Synthetic product has poor efficacies, more side effects, and gives scope for recurrence of symptoms. As the scalp is one of the most absorbent parts of the body, products applied to the scalp go directly to the blood, without being filtered in any way. Hence, it is very important to know and understand the effects of ingredients used in shampoo formulations.